Bradykinin in Hemipepsis ustulata: A novel method for safely milking wasps. (July 2016) - White, Shawn R.; Kadavakollu, Samuel
Abstract: Wasp venom characterization is of interest across multiple disciplines such as medicinal chemistry and evolutionary biology. A simple method is described herein to milk wasp venom without undue risks to the researcher. The wasps were immobilized by cooling for safe handling, restrained, and their venom was collected on parafilm. Bradykinin from Hemipepsis ustulata was identified by LC-MS/MS during method verification. Highlights: A novel method of venom collection from wasps is presented. The method is safe and can be used multiple times on a single individual. Bradykinin is identified in Hemipepsis ustulata by LC-MS/MS.